Performance and Emissions of 1.3L and 1.6L Engines Fueled with Gasoline and CNG at Several Vehicle Speeds - Sarwani, Muhamad Khairul Ilman; Fawzi, Mas; Mokhtar, Muhamad Hanif; Osman, Shahrul Azmir (The Mattingley Publishing Co., Inc., 2020)
The main objective of this work was to investigate a comparison between engine performance and exhaust emissions for 1.3L and 1.6L 4-cylinder engines fueled with gasoline or compressed natural gas (CNG). The test engines were fitted with the same CNG conversion kit, which operated with either gasoline or CNG. The engine performance and exhaust emissions were measured over vehicle speeds at 30 km/h, 50 km/h, 70 km/h, 90 km/h, and 100 km/h, with half throttle valve position. The results showed that brake powers decreased at an average of 25.18% and 33.94% when using CNG fuel. There is also a reduction in brake specific energy consumptions at an average of 17.25% for 1.3L engines. However, there is an increment of brake specific energy consumption at a lower speed for 1.6L engine fueled with CNG. The 1.3L engine produces higher exhaust gas temperatures at an average of 5.14% when running on CNG. The exhaust emissions of the 1.6L engine fueled with CNG showed higher HC, CO, O2, NOx and lower CO2 compared to the 1.3L engine fueled with the same fuel.